De novo convulsive status epilepticus in patients with multiple sclerosis treated with dalfampridine. (April 2019) - Panicucci, Emilie; Cohen, Mikael; Bourg, Veronique; Rocher, Fanny; Thomas, Pierre; Lebrun, Christine
Background: Dalfampridine extended release (DAL) is a broad-spectrum voltage-gated potassium channel blocker that is indicated in multiple sclerosis to improve the nerve conduction of demyelinated axons. Seizures are a known side effect of DAL, which is contraindicated in patients with a history of epilepsy. Objective: Three cases of multiple sclerosis (MS) with de novo convulsive status epilepticus (CSE) probably related to dalfampridine administration are described. Methods: No patients had a history of seizures or renal impairment. Biological tests were normal. A brain magnetic resonance imaging (MRI) showed diffuse cortical and subcortical atrophy without active inflammatory lesions. Results: All three patients presented with CSE that was attributed to DAL and so was discontinued. Conclusion: These case reports illustrate that, aside from seizures, de novo CSE is a potential complication of MS patients treated with DAL.